2002
DOI: 10.1007/bf02573066
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment variation in a prospective, randomized trial of chemoradiotherapy in gastric cancer: The effect of undertreatment

Abstract: MI, a measure of unresected regional nodal disease in gastric cancer, proved an independent predictor of survival. Surgical undertreatment, as observed in this trial, clearly undermined survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(89 citation statements)
references
References 26 publications
4
80
0
5
Order By: Relevance
“…Subsequently, the Medical Research Council Adjuvant Gastric Infusional Chemotherapy trial showed the effectiveness of perioperative chemotherapy [10]. However, both the abovementioned trials assessed the benefits of adjuvant therapy after limited surgery only, while the type of surgical procedure adopted for the treatment of GC can influence the results of postoperative chemotherapy [11,12]. In 2007, the adjuvant chemotherapy trial of TS-1 for gastric cancer proved that adjuvant chemotherapy with S-1 in Japan is an effective adjuvant treatment for patients who have undergone D2 lymphadenectomy for the treatment of locally advanced GC [13].…”
Section: Introductionmentioning
confidence: 98%
“…Subsequently, the Medical Research Council Adjuvant Gastric Infusional Chemotherapy trial showed the effectiveness of perioperative chemotherapy [10]. However, both the abovementioned trials assessed the benefits of adjuvant therapy after limited surgery only, while the type of surgical procedure adopted for the treatment of GC can influence the results of postoperative chemotherapy [11,12]. In 2007, the adjuvant chemotherapy trial of TS-1 for gastric cancer proved that adjuvant chemotherapy with S-1 in Japan is an effective adjuvant treatment for patients who have undergone D2 lymphadenectomy for the treatment of locally advanced GC [13].…”
Section: Introductionmentioning
confidence: 98%
“…A ressecção cirúrgica permanece a única opção terapêutica com possibilidade de cura. No entanto, existem temas controversos no manejo desses pacientes, tais como a extensão da ressecção gástrica, a extensão da dissecção linfonodal e a utilização de alternativas terapêuticas adjuvantes (quimio e/ ou radioterapia) [2][3][4] . Os avanços nos cuidados pré e pós-operatórios, o desenvolvimento dos antibióticos e o suporte das unidades de tratamento intensivo que ocorreram durante as últimas décadas fizeram com que a mortalidade pós-operatória diminuísse de índices superiores a 50% para níveis abaixo de 1% no Japão 5 .…”
unclassified
“…Although the study protocol recommended D2 lymphadenectomy and included appropriate instructions, 54% of the study patients underwent a ‘less than D1' lymphadenectomy. As reported in a second publication by the same group of authors, surgical undertreatment clearly undermined survival [30]. Therefore, one may presume that adjuvant chemoradiation did not more than compensate to a certain extent for the sequelae of inadequate surgery.…”
Section: Adjuvant Chemoradiationmentioning
confidence: 79%